Munculnya Digital Influencer Merubah Perilaku Konsumen Pada Promosi Produk, Pemilihan Produk, dan Keputusan Pembelian Generasi Milenial: Studi Pada Akun YouTube Ria SW - Grace Putlia; Nataya Niken Thioanda (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2020)
Indonesia shows a change in the behavior patterns of modern consumers who rely on social media sites to get information and reviews of desired products. In line with this, an interesting phenomenon is that after going through a pre-test, Bunda Mulia University students belonging to the millennial generation claimed that a lot of information on where to eat their destination came from digital influencers that they often watched through YouTube. Qualitative research with case study design was used as a research design. The results of the study stated that the 19 informants namely students in the millennial generation gave the same statement regarding digital influencers that indeed changed their consumer behavior, especially on the YouTube Ria SW account. The difference lies in the reason - behavioral variables, namely: digital influencers, products, and reference groups that have a direct impact.